Analisis Adat Kematian Suku Toraja Menggunakan Teori Roman Jackobson Di Manado - Putri Roganda Pane; Naia Rencani Suci; Enggis Br Siagian; Melani Limbong; Shelomita Adinda Putri Komaling; Surya Masniari Hutagalung (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This study analyzes Toraja death customs using Roman Jakobson's theory of language functions. The study highlights how language functions (emotive, conative, referential, metalinguistic, phatic, and poetic) are applied in death rituals, which reflect the cultural and social values of the Toraja people. The research findings show that these death customs serve as complex communication tools, strengthen community identity, and connect the present with the past through symbolism and traditional practices.